EFL Students’ Strategies In Dealing With Speaking Anxiety In Post Pandemic Class - Munir, Munir; Talib, Ahmad; Anugrah, Ade Surya (Tamaddun Life, 2023)
The purpose of the study was to find out the strategies that the EFL students use to reduce their speaking anxiety in post pandemic class. This research is a qualitative type of research that uses qualitative descriptive method to collect the necessary data in the hope of knowing the strategies used by students in dealing with their speaking anxiety. The participants of this study included students who were in the class of XI Bahasa at SMA Negeri 1 Pangkep. In this study, there were two instruments used, namely interviews which were carried out in two stages as the main instrument and an observation activity involving two observers. The observation was carried out in the classroom while the learning activity was conducted, and the interview sessions were carried out outside of their classroom. By using a purposive sampling technique, six student representatives were selected to be interviewed. The results of the study revealed that there were seventeen methods used by students to overcome their speaking anxiety which were then categorized into six different kinds of strategies. These six strategies according to the research finding are consisting of memory strategy, cognitive strategy, compensation strategy, metacognitive strategy, affective strategy and social strategy.